2012
DOI: 10.1016/j.lindif.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Social–emotional learning profiles of preschoolers' early school success: A person-centered approach

Abstract: Examined how aspects of social-emotional learning (SEL)—specifically, emotion knowledge, emotional and social behaviors, social problem-solving, and self-regulation—clustered to typify groups of children who differ in terms of their motivation to learn, participation in the classroom, and other indices of early school adjustment and academic success. 275 four-year-old children from private day schools and Head Start were directly assessed and observed in these areas, and preschool and kindergarten teachers pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
152
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 93 publications
(115 reference statements)
14
152
1
4
Order By: Relevance
“…This strategy requires emotion understanding (i.e., being able to represent others' emotional experiences as well as their causes and consequences) which improves with age (Payton et al, 2000). The same developmental pattern was found for cognitive engagement strategies which start to develop at the age of 4 and improve with age (Denham et al, 2012). This strategy involves emotion representation (Stegge et al, 2004), which may explain this developmental pattern.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This strategy requires emotion understanding (i.e., being able to represent others' emotional experiences as well as their causes and consequences) which improves with age (Payton et al, 2000). The same developmental pattern was found for cognitive engagement strategies which start to develop at the age of 4 and improve with age (Denham et al, 2012). This strategy involves emotion representation (Stegge et al, 2004), which may explain this developmental pattern.…”
Section: Discussionmentioning
confidence: 80%
“…When further analysing the content of the humor strategies both parents and children pointed out humor as a way to distract the target's attention away from the situation. Future research may explore whether humor conceptualized as reappraisal may only develop in older children and adolescents, given that reappraisal is more commonly used by older children and adolescents compared to younger children (e.g., Denham et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors then examined how profile membership predicted achievement in the fifth grade. Although research using variable-centred approaches have generally concluded that socioemotional skills are nonsignificant predictors of later achievement (Duncan et al 2007), a recent study using a person-centred approach has found that socioemotional skills predict academic success when they are present in students with poor cognitive control (Denham et al 2012). This finding highlights the potential usefulness of applying person-centred approaches which are better suited for taking into account multiple and correlated characteristics of children.…”
Section: Introductionmentioning
confidence: 99%
“…Getting used to the social group represented by the pre-school / school institution is associated with the child's social-emotional profile (Denham et al, 2012), defined as the ability of socio-emotional learning, awareness of one's own emotions, social behaviors and emotional self-regulation. Such noncognitive abilities (Lipnevich, Roberts, 2012), including emotions, impulses and relationships with others, appear to be linked to the early experiences of the child, which draws attention to the importance of the emotional state of the pre-school child when we refer to his/ her ability to adapt to the pre-school environment (Knitzer, Raver, 2002).…”
Section: Introductionmentioning
confidence: 99%